Online and offline corporate brand images: do they differ? - Alwi, S. F. S.; da Silva, R. V. (Corporate Reputation Review, 2008)
This study compares the corporate brand images (CBI) of two book retailers: one that sells exclusively online and the other that sells exclusively offline. The study has adopted measurements developed by Davies et al. (2004) known as the ‘Corporate Character Scale’ in order to measure the two bookstores' CBI. The study is informed by 511 responses from experienced customers of these two bookstores. To identify the difference between offline and online CBI, confirmatory factor analysis was used. Previous literature stresses that Agreeableness and Enterprise were the two most significant variables in predicting online and offline CBI. This study, however, found that consumers appeared to view online CBI as more Informal and Innovative than offline CBI (which appeared to be expressed more in terms of Agreeableness and Competence). In general, the present study adds to the existing literature in branding and reputation in two main ways. First, it puts the concept of emotional brand attributes (the CBI) in a unique context (the internet), and compares it with the bricks-and-mortar context. The present study provides empirical evidence in the context of internet and retail bookstores to enhance the understanding of branding and reputation. Secondly, the practical contribution of the study and its managerial implications can be seen in the context of defining strategy and positioning the corporate brand in the online and offline contexts.